Peningkatan Pendapatan Petani Melalui Integrasi Kakao-Ternak Kambing di Desa Tapango Barat Kecamatan Tapango Kabupaten Polewali Mandar Provinsi Sulawesi Barat - Harli A. Karim; Haeruddin Haeruddin (Jurnal Indonesia Mengabdi, 2019)
Efforts to increase the opinion of the people of Tapango Barat Village, especially partner communities, need attention. Increasing the ability of farmers to manage their land can be one way to improve the lives of partners. Integrated cocoa-goat livestock activities can increase farmers' income. Plant fertilizer needs can be obtained from the results of manure so that farmers do not need to pay for buying chemical fertilizers, besides being expensive, they are also less environmentally friendly. In addition, goats get feed from the results of cocoa leaf trimming and protective trees which are also found in cocoa plantations. Partner farmers, in turn, benefit from cocoa and goats and from saving on fertilizer costs. Implementation of activities by placing goat cages between cocoa plants so that the resulting output can overcome problems regarding fodder far from the location of the cage. Another solution is to plant a cocoa tree that is prepared for goat's feed. Various trainings have been conducted on partners including: Goat Husbandry Training, Maintenance Engineering Training on cocoa plants, Training and practice of composting made from goat manure and cocoa waste.